REDUCTION OF HEAT GAINS TO GEOTHERMAL HEAT EXCHANGERS IN LONG-TERM OPERATION - Viacheslav Yu. Polovnikov; Sofia D. Shelemekhova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Link for citation: Polovnikov V.Yu., Shelemekhova S.D. Reduction of heat gains to geothermal heat exchangers in long-term operation. Bulletin of the Tomsk Polytechnic University. Geo Аssets Engineering, 2023, vol. 334, no. 9, рр. 18-24. In Rus.